Pictionary as a didactic tool to teach english language vocabulary to Pre K Students - Pavón, Junieth (UDELAS, 2019)
The aim of this project is to find out that Pictionary is a usefui didactic technique for teaching English vocabulary in Kindergarten students of Centro Educativo Tesoros Divinos ,San miguelito morning schift